Ortaokul matematik öğretmenlerinin ölçme ve değerlendirme tekniklerine yönelik görüşleri ve özyeterlik inançlarının incelenmesi - Demirel, Gülseren (My University, 2016)
ORTAOKUL MATEMATİK ÖĞRETMENLERİNİN ÖLÇME VE DEĞERLENDİRME TEKNİKLERİNE YÖNELİK BİLGİLERİ VE KULLANMA NEDENLERİ Araştırmanın amacı; ortaokul matematik öğretmenlerinin ölçme ve değerlendirme teknikleri konusundaki bilgi düzeylerini belirlemek, öğretmenlerin kullandıkları ölçme ve değerlendirme tekniklerini tercih nedenlerini tespit etmek, bu teknikleri kullanırken karşılaştıkları güçlükleri ve teknikleri kullanma sıklıklarını belirlemek, öğretmenlerin ölçme ve değerlendirme tekniklerine yönelik özyeterlik düzeylerini tespit etmek, tekniklerden beklenen ve sağlanan faydalar ile ilgili öğretmenlerin konu hakkındaki görüşlerini almaktır. Araştırmanın örneklemini İstanbul’daki özel ve devlet eğitim kurumlarındaki ortaokullarda görev alan 96 matematik öğretmeni oluşturmuştur. Çalışma grubu, amaçlı örnekleme yöntemlerinden “benzeşik (homojen) örnekleme” yöntemi ile seçilmiştir. Öğretmenlerin seçilmesinde, gönüllük ilkesi dikkate alınmıştır. Araştırmanın verileri araştırmacı tarafından öğretmenlere 2015–2016 eğitim öğretim yılı ikinci yarısında anket çalışması uygulanarak elde edilmiştir. Elde edilen verilerin çözümü için bir istatistiksel paket programından yararlanılmıştır. Matematik öğretmenlerine uygulanan anket formundaki sorular frekans ve yüzde kullanılarak yorumlanmıştır. Öğretmenlerle yapılan görüşmeler de kodlanarak bu görüşmelerin ortak sonuçları çıkarılmıştır. Araştırma bulguları dikkate alındığında; ankete katılan öğretmenlerin ölçme ve değerlendirme teknikleri konusunda bilgi düzeylerinin iyi seviyede olduğu, bu teknikleri kullanma sıklıkları açısından göze çarpan büyük farklılıklar olmadığı, hemen hemen her tekniğin kullanıldığı, tekniklerin kullanışlı ve pratik olmasının tercih sebebini etkilediği göze çarpmıştır. Ayrıca öğretmenlerin ölçme ve değerlendirme tekniklerinin gerekliliğinin farkında oldukları ve bu konudaki yeniliklere açık oldukları görülmektedir. Araştırmanın sonuçları dikkate alınarak matematik eğitiminde tamamlayıcı ölçme ve değerlendirme araçlarının uygulanması konusunda gözlenen aksaklıkların giderilmesine yönelik birtakım önerilerde bulunulmuştur. Matematik, Matematik Eğitimi, Matematikte ölçme ve değerlendirme, Tamamlayıcı ve Geleneksel Ölçme ve Değerlendirme, Alternatif Ölçme ve Değerlendirme, Ölçme ve Değerlendirme Araçları, Ölçme ve Değerlendirme Teknikleri

In the period of education and training, behaviors that a person has or has not in targeted behaviors change’s direction, level and the deficiencies in this subject are converted to understandable level with assessment and evaluation. This characteristic of assessment and evaluation makes it the most important part of education and training. According to results in accordance with the explanations; teachers are need to know every skills and abilities about assessment and evaluation (Işık, 2009). According to some results that were obtained from different studies; because of unwillingness of teachers, lack of information of methods and techniques, crowded class sizes, lack of time, previous beliefs about assessment and evaluation, lack of sources and equipment, applications of assessment and evaluation techniques were not able to be used in an effective way. (Carnevale, 2006).This situation shows that assesment and evaluation process which is the most important part of curriculums couldn’t be applied effectively. When it is analyzed, studies that have been done in Turkey for secondary school Math teaching programs in assessment and evaluation, it has been observed that assessment and evaluation is one of the most difficult dimensions of teaching. ( Bal and Doğanay, 2010). At this study, specifying secondary school mathematics teachers’ knowledge level about supplementary evaluation techniques and which of these techniques they prefer, and the reasons of preference of these techniques have been intended for. In this context, What are the levels of secondary school mathematics teachers’ knowledge about supplementary evaluation techniques and reasons of choice for these techniques?”. This question has been the focus of this study. Participants of the study consist of teachers of public and private schools, 50 from each. To gather data a questionnaire with three parts was formed. First and second parts of the questionnaire is about frequency of teachers’ using assessment and measurement techniques and whether they have sufficient knowledge to use these techniques respectively. Third part is about the reason why the teachers prefer supplementary assessment and measurement techniques. Data collection tools were formed according to the literature. Then, these tools were modified in accordance with the comments of two experts. Lastly, final changes were applied based on the data obtained from pilot study. Moreover, at the last part of the study semi-constructed interviews were made with six of the teachers. Acquired data has been analyzed by content analysis. While the content analysis has been done data acquired from questionnaires and reports towards the aims of the study have been categorized by the help of some codes specified before. After that, codes connected with each other have been analyzed under different theme (Yıldırım ve Şimşek, 1999). Evaluation of the data has shown that about the supplementary evaluation approaches primary school mathematics teachers can make objective evaluations using these techniques and involve students in the evaluation process. The teachers had positive thoughts about the effectiveness of using these techniques. On the other hand, they had negative thoughts as well such as their being time consuming and difficult to apply in each classroom. Furthermore, it has been observed that these techniques are not used for their purposes. It has been observed that secondary school math teachers often prefer project assignments, multiple choice questions, and open-ended questions, whereas they rarely used math diaries and check lists. As the reason of rare use of these techniques factors such as time problem, intensive curriculum, crowded classrooms, excessive involvement of parents, difficulties in archiving evaluation tools have come forward. Key Words: Mathematics, Mathematics Education, Assessment and Evaluation in Mathematics, Complementary and Traditional Assessment and Evaluation, Alternative Assessment and Evaluation, Assessment and Evaluation Tools, Assessment and Evaluation Techniques
Keywords: Eğitim; Eğitim ve öğretim (İlk); Matematik; Ölçme ve değerlendirme; Türkiye